Taking time, breaking codes: moments in white teacher candidates' exploration of racism and teacher identity. Issue 8 (13th September 2016) - Mason, Ann Mogush
Abstract: In three narrative vignettes, this paper challenges scholars and practitioners of teacher education to consider ways that our courses do and do not engage white teacher candidates to take on racially conscious orientations. The work addressed in this paper has implications for our understandings of how preservice teachers can learn about racial identity in ways that benefit individual teachers and support their work in schools and communities. These findings buttress previous work in 'second wave' white teacher identity research and can translate directly into teacher education course and program design. Simultaneously, this research speaks to the broader literature in teacher education, offering evidence to support the value of extended periods of time for new teachers to build authentic relationships and conduct critical study of self and society in a climate where teacher preparation programs face pressure to reduce credits to degree and intensify their focus on preparing students for externally mandated assessments.